Dos crimes de violação de direitos de autor - Paula, Fernando Shimidt de (2009)
The aim of this paper is to expose the evolution of the penal treatment that is given to the violation of the copyright in Brazil. Considering some historical events emphasizing Brazilian penal legislation since the Portuguese Ordinations , an effort was made to show how the harmful practices against the intellectual property occurred, the way society has treated them and how the social and political life in Brazil was also affected. Since the increase given by Queen Anne of England in 1710 until the present period it is possible to notice that from the confiscation to the penalty prison, the counterfeiters deserve more attention from the legislators, due to the human development and the international conventions about this issue, where Brazil takes part of. Concerning some items on authorial right issues, (it is important to consider that authorial does not mean author s right in this case) about counterfeits and the public dominion and also several doctrine manifestations about law of these institutes and its crimes, going through the analyses of the constitutional and infra-constitutional treatment of the subject, emphasizing the article 184 of the Penal Code, a basic rule about the issue and the aim of this study, considering what the Laws number 9.279/96 and 9.609/98 say about violation of trade mark and invention rights, as well as computer programs. Finally, a connection was made between piracy - a commercial form of counterfeit and the economical activities of crime organization, and also some efficient forms of fighting against this modality of crime, bringing some statistics up